PENGARUH METODE TUTOR SEBAYA BERBASIS VIDEO YOUTUBE TERHADAP SIKAP KEMANDIRIAN BELAJAR MAHASISWA PGSD UNISRI - Jumanto, Jumanto; Prihatsari, Ema Butsi (Profesi Pendidikan Dasar, 2018)
Abstract: The aims of this research was to determine: (1) difference of attitude of self-reliance learning of PGSD UNISRI students between before and after using peer tutor based on Youtube videos method and (2) effectiveness of using peer tutor based Youtube videos method toward independence attitude of PGSD student of UNISRI. The data of this research are primary data, obtained from questionnaire and documentation. This research is an experimental research. This research used One Group Pretes Posttes Design. Population in the study were all students of PGSD UNISRI Academic year 2016/2017. Sampling technique used in this research is purposive sampling. Instrument validity is tested by means of Construct Validity. Data were analyzed by t-test and N-gain test. T test results obtained sig (2-tailed) of 0,000 whose value is less than 0.05. This means rejecting Ho and it can be concluded that there is a significant difference in the attitude of learning independence before and after using peer tutor based Youtube videos methods. Result of calculation with N-gain that is equal to 0,734 which means effectiveness of using peer tutor based Youtube videos method in improving attitude of independence learn at high criterion.